The Impact on the Long-term Outcomes of Hormonal Status After Hepatic Resection for Breast Cancer Liver Metastases - BACALBASA, NICOLAE (In Vivo, 2018)
Background/Aim: Breast cancer remains one of the most frequently encountered malignancies worldwide, which is in most cases diagnosed in early stages of disease. However, although surgery and adjuvant oncological treatment are performed with curative intent, a certain number of cases will develop distant metastases. In cases presenting oligometastatic disease, surgery might be tempted in order to maximize the benefit in terms of survival. The aim of this paper was to identify which cases could benefit most after liver resection for breast cancer liver metastases. Materials and Methods: The study included 67 patients submitted to surgery for breast cancer liver metastases between 2003 and 2017 in the “Dan Setlacec” Center of Gastrointestinal Diseases and Liver Transplantation, Fundeni Clinical Institute. Results: Patients diagnosed with hormone-positive breast tumors reported a significantly higher disease-free and overall survival after resection of the primary tumor. After resection for breast cancer liver metastases, patients presenting hormone receptors at the level of the metastatic sites also experienced a better outcome when compared to those in which hormonal receptors were absent. However, the difference was not statistically significant. Conclusion: Liver resection for breast cancer liver metastases seems to be associated with the best outcomes in terms of survival in patients presenting positive hormonal receptors status